1999
DOI: 10.1021/jp982538l
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Catalytic Cracking Activity of Hexane over H−ZSM-5, H−β and H−Y Zeolites

Abstract: Mono-and bimolecular intrinsic rate constants for the conversion of n-hexane over H-Y, H-ZSM-5, and H-β zeolites were measured at 623 K by combining conventional catalytic techniques with gravimetric adsorption measurements. Since H-zeolites are catalytically active, their adsorption properties under reaction conditions could not be directly obtained. Rather, adsorption experiments were carried out on the H-zeolites at temperatures below the onset of catalytic activity (450-530 K). Thermodynamic adsorption con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 25 publications
7
91
0
Order By: Relevance
“…This analysis of the cracking reactions is in good agreement with those previously made for the monomolecular cracking pathway for n-hexane [25,28,31].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This analysis of the cracking reactions is in good agreement with those previously made for the monomolecular cracking pathway for n-hexane [25,28,31].…”
Section: Resultssupporting
confidence: 90%
“…Within the experimental uncertainties, the product distributions are identical for all zeolites and are consistent with those previously reported for monomolecular cracking of n-hexane, which are also given in Table 2 [25,31]. For the monomolecular pathway, the primary product of protolysis gives unity molar ratio of methane versus pentene, C 2 versus C 4 (either ethylene plus butane or ethane and butene), propane versus propene, and hydrogen versus hexene.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…where K H is the Henry constant (and thus equals the gradient of the isotherm plots at low coverage Lercher, 1997; Kotrel et al, 1999;Denayer et al, 1997). It can be seen that there is an increase in adsorption strength with chain length.…”
Section: Measurement Of Equilibrium Adsorption Isothermsmentioning
confidence: 99%
“…Likewise, structural isomerization of hydrocarbons has been shown to proceed via the same reaction intermediates as cracking [143,144], but under low temperature isomerization conditions, the reactive carbenium ions accept a hydride and desorb before C-C scission can occur. In a previous study, H-ZSM-5 was shown to be two orders of magnitude more active compared to H-Y for n-hexane cracking at 623 K and an n-hexane partial pressure of 5.3 kPa [145]. In addition, unlike in larger-pore catalysts, where isomerized products can easily diffuse out of the solid framework, in H-ZSM-5 branched alkanes preferentially adsorb at the intersections and undergo a jump mechanism for diffusion.…”
Section: Discussionmentioning
confidence: 96%